Cyclization of Diazoacetamides Catalyzed by N-Heterocyclic Carbene Dirhodium(II) Complexes - Gomes, Luis F. R. (2015)
The axial coordination of N-heterocyclic carbene ligands onto dirhodium(II) complexes was examined, together with its role in the intramolecular C-H insertion reactions of alpha-diazoacetamides. The formation of a decarbonylated product occurs by a free-carbene mechanism in which the structures of the catalyst and the acetamide play a decisive role.. - Fundacao para a Ciencia a Tecnologia [POCI 2010]; FEDER [PTDC/QUI/66695/2006, PTDC/QUI/66015/2006, SFH/BPD/46589/2008, SFRH/BD/30619/2006]. - We thank to Fundacao para a Ciencia a Tecnologia (POCI 2010) and FEDER (PTDC/QUI/66695/2006, PTDC/QUI/66015/2006, SFH/BPD/46589/2008 and SFRH/BD/30619/2006) for their financial support, and the Portuguese NMR Network (IST-UTL Center) for providing access to the NMR facility.